Citrobacter amalonaticus inhibits the growth of Citrobacter rodentium in the gut lumen - Mullineaux,Sanders C; Carson,D; Hopkins,E; Glegola-Madejska,I; Escobar-Zepeda,A; Browne,H; Lawley,T; Frankel,G (mBio, 2021)
The gut microbiota plays a crucial role in susceptibility to enteric pathogens, including Citrobacter rodentium, a model extracellular mouse pathogen that colonizes the colonic mucosa. C. rodentium infection outcomes vary between mouse strains, with C57BL/6 and C3H/HeN mice clearing or succumbing to the infection respectively. Kanamycin (Kan) treatment at the peak of C57BL/6 mouse infection with Kan-resistant C. rodentium resulted in re-localisation of the pathogen from the colonic mucosa and cecum to solely the cecal luminal contents; cessation of the Kan treatment resulted in rapid clearance of the pathogen. We now show that in C3H/HeN mice, following Kan-induced displacement of C. rodentium to the cecum, the pathogen stably colonizes the cecal lumen of 65% of the mice in the absence of continued antibiotic treatment, a phenomenon we term antibiotic-induced bacterial commensalisation (AIBC). AIBC C. rodentium was well-tolerated by the host, which showed little signs of inflammation; passaged AIBC C. rodentium robustly infected naïve C3H/HeN mice suggesting that the AIBC state is transient and did not select for genetically avirulent C. rodentium mutants. Following withdrawal of antibiotic treatment, 35% of C3H/HeN mice were able to prevent C. rodentium commensalisation in the gut lumen. These mice presented a bloom of a commensal species, Citrobacter amalonaticus, which inhibited the growth of C. rodentium in vitro in a contact-dependant manner, and luminal growth of AIBC C. rodentium in vivo. Overall our data suggest that commensal species can confer colonization resistance against closely-related pathogenic species.